PG102 Upregulates IL-37 through p38, ERK, and Smad3 Pathways in HaCaT Keratinocytes - Hyun-keun Kim; Seonung Lim; Min-Jung Bae; Wonwoo Lee; Sunyoung Kim (Mediators of Inflammation, 2019)
IL-37 is an immunomodulatory cytokine that suppresses inflammation in various cell types and disease models. However, its role in keratinocytes has not been clearly understood, and there has been no report on the agents that can increase the expression of IL-37 in keratinocytes. In this study, we investigated the effects of silencing IL37 in HaCaT keratinocytes and the molecular mechanisms involved in the upregulation of IL-37 by PG102, a water-soluble extract from Actinidia arguta. It was found that knockdown of IL37 resulted in the augmented expression of antimicrobial peptides (AMPs) in response to cytokine stimulation. PG102 increased the expression of IL-37 at both mRNA and protein levels presumably by enhancing the phosphorylation of Smad3, ERK, and p38. Indeed, when cells were treated with specific inhibitors for these signaling molecules, the expression level of IL-37 was reduced. PG102 also promoted colocalization of phospho-Smad3 and IL-37. Our results suggest that IL-37 inhibits the expression of AMPs and that PG102 upregulates IL-37 through p38, ERK, and Smad3 pathways in HaCaT cells.